The challenges of treating osteoarthritis pain and opportunities for novel peripherally directed therapeutic strategies. (1st August 2022) - Gonçalves, Sara; Gowler, Peter R.W.; Woodhams, Stephen G.; Turnbull, James; Hathway, Gareth; Chapman, Victoria
Abstract: Osteoarthritis (OA) is a chronic joint disease that represents an increasingly substantial global burden. Joint pain is the most significant symptom of OA. Unfortunately, current pharmacological treatments for OA pain are often not wholly efficacious, or are associated with serious adverse effects. This lack of effective pain relief has seen the prescription of opioids for OA pain increase over the past decades. The long-term adverse effects of prescribed opioids alongside the increasing prevalence of OA pain highlights the need for alternative analgesics. Understanding the mechanisms that drive this chronic joint pain is crucial for the development of novel analgesics. OA is a heterogeneous disease, and this is reflected by the diversity of pain phenotypes in people with the disease. Herein, we review current understanding of the biological changes at the joint and within the central nervous system that drive this chronic pain. We particularly focus on the most recent advances in our understanding of the peripheral nociceptive mechanisms that underlie chronic OA pain and highlight how targeting peripheral OA inflammation may open up opportunities for novel analgesics. Highlights: Chronic joint pain in osteoarthritis (OA) is a global clinical burden. Current treatments are inadequate, providing insufficient pain relief. This review covers recent advances in peripheral and central mechanisms of OA pain. Understanding these mechanisms will aid development of novel analgesics.